A Simple yet Effective Semi-Anechoic Chamber for the Acoustic Characterization of an LSRA - Salvado, José (2019)
This paper presents a simple and cost effective solution of a semi-anechoic chamber suitable for the acoustic noise characterization of a Linear Switched Reluctance Actuator (LSRA). Using simple construction and assembling techniques, and low-cost materials, it allows significant acoustic isolation characteristics from the environmental noise, caused by people´s activities, other machinery operation, etc. The average attenuation achieved is better than 30 dB for a noise source placed at 1 meter distance from its walls. The overall test results demonstrate an affordable yet effective semi-anechoic chamber solution, and prove its adequacy for the specific purpose of characterizing a LSRA in terms of the acoustic noise produced.